Pharmacological characterization of novel synthetic opioids: Isotonitazene, metonitazene, and piperidylthiambutene as potent μ-opioid receptor agonists. (15th December 2022) - De Luca, Maria Antonietta; Tocco, Graziella; Mostallino, Rafaela; Laus, Antonio; Caria, Francesca; Musa, Aurora; Pintori, Nicholas; Ucha, Marcos; Poza, Celia; Ambrosio, Emilio; Di Chiara, Gaetano; Castelli, M. Paola
Abstract: Recent trends of opioid abuse and related fatalities have highlighted the critical role of Novel Synthetic Opioids (NSOs). We studied the μ-opioid-like properties of isotonitazene (ITZ), metonitazene (MTZ), and piperidylthiambutene (PTB) using different approaches. In vitro studies showed that ITZ and MTZ displayed a higher potency in both rat membrane homogenates (EC50 :0.99 and 19.1 nM, respectively) and CHO-MOR (EC50 :0.71 and 10.0 nM, respectively) than [D-Ala 2, NMe-Phe 4, Gly-ol 5 ]-enkephalin (DAMGO), with no difference in maximal efficacy (Emax) between DAMGO and NSOs. ITZ also has higher affinity (Ki:0.06 and 0.05 nM) at the MOR than DAMGO in both systems, whilst MTZ has higher affinity in CHO-MOR (Ki=0.23 nM) and similar affinity in rat cerebral cortex (Ki = 0.22 nM). PTB showed lower affinity and potency than DAMGO. In vivo, ITZ displayed higher analgesic potency than fentanyl and morphine (ED50 :0.00156, 0.00578, 2.35 mg/kg iv, respectively); ITZ (0.01 mg/kg iv) and MTZ (0.03 mg/kg iv) reduced behavioral activity and increased dialysate dopamine (DA) in the NAc shell (max. about 200% and 170% over basal value, respectively. Notably, ITZ elicited an increase in DA comparable to that of higher dose of morphine (1 mg/kg iv), but higher than the same dose of fentanyl (0.01 mg/kg iv). In silico, induced fit docking (IFD) and metadynamic simulations (MTD) showed that binding modes and structural changes at the receptor, ligand stability, and the overall energy score of NSOs were consistent with the results of the biological assays. Highlights: ITZ, MTZ showed high potency and affinity at MOR in native and recombinant system. ITZ reduced nociception and behavioral activity when compared to morphine or fentanyl. ITZ and MTZ stimulate in vivo DA transmission in the NAc shell. ITZ and MTZ displayed in silico properties consistent with the biological assays.